IMPLEMENTASI TOLERANSI UMAT BERAGAMA SEBAGAI PILAR KEHARMONISAN DALAM PENDIDIKAN ISLAM MASYARAKAT MULTIKULTURAL DI KABUPATEN BENGKALIS - Suheryeni; Chanifudin (EL-TA’DIB: Journal of Islamic Education, 2025)
This article aims to examine in depth the concept of religious tolerance and its implementation as a pillar of harmony in the life of a multicultural society. The discussion focused on the definition of tolerance according to experts, tolerance from the perspective of religion and the state, the concept of a multicultural society, and forms of implementation of religious tolerance in daily life. In addition, this paper also discusses the challenges faced in the implementation of religious tolerance and the efforts that can be made to strengthen tolerance in a pluralistic society. The writing method used in this article is a literature study method, which is by examining and analyzing various relevant literature sources, such as scientific books, journals, laws and regulations, and official documents related to tolerance, multiculturalism, and religious life in Indonesia. This approach is used to gain a comprehensive theoretical and conceptual understanding of tolerance The implementation of religious tolerance in people's lives can be realized through various forms of real behavior, such as respecting the implementation of other religious worship, not imposing beliefs, establishing interfaith cooperation in social activities, maintaining attitudes and speech so as not to offend followers of other religions, and using social media wisely. The implementation of tolerance in daily life also requires dialogue between religious communities, deliberation in resolving differences, and the active role of educational institutions, families, and the government in instilling the values of tolerance from an early age. Keywords: Tolerance, Harmony, Islamic Education, Multicultural